The role of learner control and psychological ownership for self-regulated learning in technology-enhanced learning designs - Ilona Buchem; Gemma Tur; Tobias Hoelterhof (Interaction Design and Architecture(s), 2020)
Theory and research show that psychological ownership has an important impact on how individuals engage, react to change and invest themselves into activities. Drawing on the theory of psychological ownership and self-regulated learning, this study explores the role of psychological ownership for selfregulated learning in context of technology-enhanced learning in four courses at two universities in Germany and Spain. We employ a research model which explains the route from perceived control of the learning environment to psychological ownership and from psychological ownership to self-regulated learning, drawing on previous research in Personal Learning Environments. We examine differences in learning designs and explore how these may be related to different perceptions of control and ownership. This study helps to apply and extend the theory of psychological ownership to the field of technology-enhanced learning with focus on e-portfolio practices in higher education while providing practical insights for creating and implementing learning designs which promote learner control, ownership and self-regulated learning.